Advancements in PSMA ligand radiolabeling for diagnosis and treatment of prostate cancer: a systematic review - Yan, Yuanzhuo; Zhuo, Huixian; Li, Tengfei; Zhang, Jintao; Tan, Min; Chen, Yue (Frontiers in Oncology, 2024)
Prostate cancer(PCa), a leading global health concern, profoundly impacts millions of men worldwide. Progressing through two stages, it initially develops within the prostate and subsequently extends to vital organs such as lymph nodes, bones, lungs, and the liver. In the early phases, castration therapy is often employed to mitigate androgen effects. However, when prostate cancer becomes resistant to this treatment, alternative strategies become imperative. As diagnostic and treatment methodologies for prostate cancer continually advance, radioligand therapy (RLT) has emerged as a promising avenue, yielding noteworthy outcomes. The fundamental principle of RLT involves delivering radionuclide drugs to cancerous lesions through specific carriers or technologies. Subsequently, these radionuclide drugs release radioactive energy, facilitating the destruction of cancer cell tissues. At present, the positron emission tomography (PET) targeting PSMA has been widely developed for the use of diagnosis and staging of PCa. Notably, FDA-approved prostate-specific membrane antigen (PSMA) targeting agents, such as 68 Ga-PSMA-11 and 177 Lu-PSMA-617, represent significant milestones in enhancing diagnostic precision and therapeutic efficacy. This review emphasizes the current research status and outcomes of various radionuclide-labeled PSMA ligands. The objective is to provide valuable insights for the continued advancement of diagnostic and therapeutic approaches in the realm of prostate cancer.